Reformulating the Reversal of the Burden of Proof in Corruption Cases: Integrating Positive Law and Islamic Legal Principles - Riady, Roy; Febrian, Febrian; Nashriana, Nashriana; Yusuf, M (Nurani, 2025)
Corruption, as an extraordinary crime, necessitates the application of a reversed burden of proof mechanism. However, its procedural implementation remains problematic and potentially infringes upon the rights of the accused. The urgency of this study lies in the need for a balanced legal reformulation, one that strengthens the effectiveness of anti-corruption efforts while upholding the Islamic conception of justice, particularly the principle of ḥifẓ al-māl (protection of wealth) as an essential element of maqāṣid al-syarī‘ah. This research analyzes theories of criminal evidence, the presumption of innocence, and the balanced probability principle, and further compares them with legal practices in other jurisdictions. The study employs a normative-juridical method combined with statutory, case, comparative, sociological, and futuristic approaches. Primary, secondary, and tertiary legal materials are examined through deductive and inductive reasoning. The findings reveal the necessity of legal reconstruction of Article 37 of the Anti-Corruption Law and Article 77 of the Anti-Money Laundering Law to address legal gaps and to provide procedural guidelines for the application of the reversed burden of proof by prosecutors, defendants, and judges. The existing mechanism lacks standardized evidentiary parameters, resulting in an imbalance between the prosecution and the defense. Instruments such as the State Officials’ Wealth Report (LHKPN) have the potential to strengthen evidentiary processes, yet remain underutilized. Therefore, a legal reformulation is required to establish clear procedural guidelines that integrate the balanced probability principle with the values of maqāṣid al-syarī‘ah. The study recommends revising the Anti-Corruption Law, synchronizing it with the new Criminal Code, and enhancing justice- and welfare-oriented legal instruments.